2019
DOI: 10.3390/su11185016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patterns of Sustainability Stimuli of Project Managers

Abstract: Sustainable project management is becoming important and the sustainability concepts of people, the planet and profit needs to be incorporated into any type of project. This article focuses on the behavior of the project manager per se and the stimuli patterns that motivate them to adhere to sustainable project management. Three stimuli patterns are used i.e., intrinsically motivated, pragmatic and task driven. To determine which of these patterns influence a project manager, a quantitative pair-wise compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 47 publications
10
46
1
1
Order By: Relevance
“…Most recent research seems to expand to the impact of sustainable project management on (project) success (Khalifeh et al 2019;He et al 2019) and to the motivation to include sustainability in project management by project managers (Marnewick et al 2019;Silvius and de Graaf 2019;Poon and Silvius 2019) and project owners (Zhang et al 2019). Our findings are summarized in Table 2.…”
Section: Descriptive Record Of Search Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Most recent research seems to expand to the impact of sustainable project management on (project) success (Khalifeh et al 2019;He et al 2019) and to the motivation to include sustainability in project management by project managers (Marnewick et al 2019;Silvius and de Graaf 2019;Poon and Silvius 2019) and project owners (Zhang et al 2019). Our findings are summarized in Table 2.…”
Section: Descriptive Record Of Search Resultsmentioning
confidence: 78%
“…Sustainability is seen here as a part or dimension of project success (Silvius and de Graaf 2019) and not as a contributing element. Researchers encourage projects and project managers to address sustainable aspects (Goedknegt and Silvius 2012;Helgadóttir 2008;Valdes-Vasquez and Klotz 2013;Xu and Hua 2011) or call it an imperative for project management (Ghosh et al 2014), with an intrinsically motivated pattern (Marnewick et al 2019) where "the project manager is intrinsically motivated to work on a sustainable project, and to achieve sustainable results" (Goedknegt 2013b, p. 279). It is even argued that"the intrinsic type of project owners' motivation is more effective than the extrinsic type" (Zhang et al 2019, p. 651) in which "projects can contribute significantly to the mission of sustainable development" (Yao et al 2011) and that projects are conducive to sustainable development (Silvius et al 2017;Silvius 2017).…”
Section: Sustainability As Intrinsic Valuementioning
confidence: 99%
“…It is clear from the project management literature that project managers face trade-off decisions when trying to reconcile sustainabilityrelated objectives with conventional triple-constraint criteria; to date, there has been no effective exploration of the tensions that arise as a result. Most recently, research exploring the role of the project manager has identified the central and influential position project managers hold regarding decisions over sustainability matters (Marnewick et al, 2019;Poon & Silvius, 2019;Silvius & de Graaf, 2019;Silvius & Schipper, 2020). Indeed, as discussed above, the project manager's central position in the project offers the opportunity to steer the project toward multiple objectives.…”
Section: The Role Of the Project Managermentioning
confidence: 99%
“…On the other hand, challenges and barriers to be surmounted in incorporating sustainability in PM include the lack of life cycle inventory data for TEA and LCA for technology projects at their infancy and the intentional exclusion of environmental sustainability during the initial design and operation of a project because of emphasis on controlling cost and technical specifications. This was encountered in information system projects where engineering infrastructures were designed and constructed based solely on economic sustainability (Marnewick et al, 2019).…”
Section: Sustainability Inclusion In Pmmentioning
confidence: 99%
“…For R&D of bioproducts, organizational factors can be defined based on sustainability metrics as identified by project managers across different industries (Silvius et al, 2017). While bioproducts R&D projects are focused on the sustainability of product and process technology, a survey of stimulus patterns of 101 project managers (i.e., intrinsically motivated, pragmatic, and task driven) showed that they chose to incorporate sustainability because they were personally motivated to utilize tools that comply with PM competency standards and industry certifications (Marnewick et al, 2019). In another experimental study, Martínez-Perales et al (2018) concur that management system certifications in the energy sector has a significant positive impact on the success of company projects in addition to time, cost and milestones achieved during the project life cycle.…”
Section: Sustainability Inclusion In Pmmentioning
confidence: 99%